Mexican-immigrant students transforming challenges into opportunities at a border school in the United States - Skukauskaitė, Audra; Bolt, Alicia (Social Welfare: Interdisciplinary Approach, 2017)
As children of Mexican immigrant families enter schools in the United States of America, they face differences between their prior schooling experiences and the expectations in the new schools. Research on immigrant children has examined language and academic adaptation variables, yet little consideration has been given to the perspectives of children and their families and teachers. Utilizing principles of interactional ethnography, we examined elementary school student and their family and teacher perspectives about the differences between the children’s prior schooling in Mexico and their current experiences in an elementary school located in Ollin, a town in Texas, near the Mexico border. Over the course of one academic year, we interviewed ten children, eight parents, and six teachers, conducted observations in schools on both sides of the border, and collected relevant documents to examine the larger social and educational contexts participants referenced in the interviews. Using an ethnographic perspective, discourse and contrastive analyses, and triangulation of sources and types of data, we focused on children’s perspectives to uncover the challenges they faced and the ways they overcame the challenges in their new, post-migration, school in Texas. Children foregrounded two primary challenges: language and play time. However, we discovered that the children, their parents and teachers did not let the challenges stop their educational opportunities. Instead, despite the challenges, children, with support of peers, teachers, and parents, actively transformed the challenges and constructed new opportunities for learning and adapting to their post-immigration school. This paper demonstrates how focusing on children’s perspectives makes visible that children and immigrant families become active agents of change, transforming challenges into learning opportunities. In the ongoing deficit models of education and negative rhetoric about immigrants, the paper shows how the people themselves take ownership of their schooling and create social and educational welfare for themselves and others. Understanding immigrants’ active participation in their schooling has a potential to impact the ways other families, educators, and policy makers view and describe their own and others’ experiences of learning, schooling, and international migration.